The effect of short-term return reversals on momentum profits. Issue 3 (29th June 2021) - Sim, Myounghwa; Kim, Hee-Eun
Abstract : The authors investigate the effect of a short-term stock return reversal on the term structure of momentum profits in the Korean stock market following Goyal and Wahal (2015). Their empirical findings show that the term structure of momentum is more pronounced when a return reversal lasts up to two months but is substantially weakened when past performance over the last two months is not taken into account for portfolio formation. Their evidence suggests that the term structure of momentum profitability arises primarily from a carryover of the return reversal from the previous two months.